2000
DOI: 10.1097/00003226-200007000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Findings in Human Keratolimbal Allograft Rejection

Abstract: KLAL rejection is a newly recognized entity. Pathologic findings of rejected specimens indicate that this is a T-cell mediated rejection phenomenon. The pattern of cytokeratin staining provided little evidence that the epithelium covering KLALs had a corneal phenotype. The scarcity of vimentin-positive epithelial cells suggests that the stem-cell/transient-cell pool was probably depleted. Early recognition of clinical rejection is important, as treatment with immunosuppressive therapy may reverse the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…MHC Class II ϩ cells were observed mainly in the stroma and moderately in the epithelium. These findings are consistent with the study of Daya et al 14 in human eyes, which also showed large numbers of lymphocytes and MHC Class II ϩ cells in rejected limbal tissues, especially in the stroma. They suggested that cells in the stroma (macrophages) and epithelium (Langerhans cells and macrophages) were probably participating in antigen presentation.…”
Section: Discussionsupporting
confidence: 93%
“…MHC Class II ϩ cells were observed mainly in the stroma and moderately in the epithelium. These findings are consistent with the study of Daya et al 14 in human eyes, which also showed large numbers of lymphocytes and MHC Class II ϩ cells in rejected limbal tissues, especially in the stroma. They suggested that cells in the stroma (macrophages) and epithelium (Langerhans cells and macrophages) were probably participating in antigen presentation.…”
Section: Discussionsupporting
confidence: 93%
“…Investigation of the limbal graft in LSCD patients after KLAL using magnified photographic prints in the past was limited by the poor image quality due to low resolution. Some researchers have attempted to circumvent this limitation by examining the histopathology of patients' keratolimbal tissue obtained at the time of repeat surgery [19]. However, this only provides information of the transplants that have failed.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Particularly characteristic is the process of lymphocyte infiltration. 16 We observed the presence of various inflammatory cells including lymphocytes, plasma cells, and macrophages as well as vascularization.…”
Section: Discussionmentioning
confidence: 85%